How does Green Finance affect the environment in the ASEAN emerging countries? - Agustin, Isnaini Nuzula; Mahendra, Rizky Adi; Hesniati, Hesniati (Economic Journal of Emerging Markets, 2025)
Purpose — This study examines how economic growth, green finance, and renewable energy affect environmental quality (CO2 emissions) under the Environment Kuznets Curve (EKC) hypothesis framework. Methods — This study uses data from ASEAN-6 developing countries, including Indonesia, Malaysia, Thailand, Vietnam, the Philippines, and Cambodia, from 2000 to 2020. It employs Panel Autoregressive Distributed Lag (ARDL), which is widely used for time series analysis since it can capture the short-run and long-run effects among variables.Findings — The result shows the presence of the EKC Hypothesis in ASEAN developing countries. Green Finance and Renewable Energy reduce CO2 emissions only in the long run. In contrast, in the short run, Green Finance shows no effect in lowering CO2 Emissions due to initial costs, infrastructure challenges, market dynamics, and delayed policy implementation; the effect seems to increase in the long run as economies evolve, technologies mature, and awareness of environmental issues rises within emerging economies.Implication — This study suggests that ASEAN developing countries should enhance their green finance efforts and expedite the transition to renewable energy by attracting additional investments in green finance and renewable energy transition. Governments in the Southeast Asian region must improve their policies and laws. Originality — Revisiting the EKC hypothesis by including Green Finance within the ASEAN-6 emerging countries, which has been scarcely conducted in recent literature, this study contributes to the region's policymakers regarding green finance allocation and its relationship to environmental quality.